Diagnostic accuracy, characteristics and survival of children with trauma in HEMS: a retrospective multi-centre observational study - Merit Roehl; Lea Weber; Julian Klug; Benjamin Voit; Roland Albrecht; Christian P. Both; Thomas Riva; Urs Pietsch; Alexander Fuchs (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2026)
Abstract Background Trauma is a leading cause of death in children. Paediatric patients comprise only a small fraction of HEMS missions. Little is known about the diagnostic accuracy of prehospital and in-hospital diagnoses in a large physician-staffed HEMS. Methods This observational multicentre study included paediatric trauma patients ≤ 16 years treated by the Swiss Air-Rescue between 28/10/2021 and 20/08/2024. We included all primary missions with a National Advisory Committee for Aeronautics (NACA) score of ≥ 3 (i.e. moderate to severe trauma) transported to three paediatric trauma centres or declared dead on-scene. Data were obtained from the HEMS database and the hospital discharge report. The primary outcome was diagnostic accuracy between the prehospital and in-hospital diagnoses, measured with Cohen’s kappa. Secondary outcomes included patient characteristics, interventions, and survival. Results We screened 1,531 eligible missions, of which 282 met inclusion criteria. Median age was 8.3 [IQR 3.5–12.1] years, and 163 (57.8%) were male. Most missions had a NACA score of 3 [IQR 3–4] and were during the daytime (90.4%). Ten patients were declared dead on-scene. Tracheal intubation was performed in 7.5% of the patients. Cohen’s kappa of the diagnostic accuracy between prehospital and in-hospital diagnoses was 0.64 (95%CI 0.58–0.70). Polytrauma was underdiagnosed; in contrast, injuries to the extremity, pelvis and traumatic brain injury were overdiagnosed. Overall survival to hospital discharge and at 1 year after trauma was 92.2%. Conclusions Paediatric trauma in this cohort was characterised by a high incidence of high-velocity injuries. The prehospital diagnosis correlated substantially with the in-hospital diagnosis, supporting the clinical value of HEMS physicians to correctly triage paediatric patients. Documentation of vital signs was heterogeneous. Hospital survival and 1-year survival were high in this cohort. However, polytrauma remained underdiagnosed and should be targeted to improve prehospital care for paediatric trauma. Trial registration N/A.